2019
DOI: 10.1097/md.0000000000014508
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and safety of thread-embedding acupuncture for treatment of the sequelae of Bell's palsy

Abstract: Background: The sequelae of Bell's palsy cause critical problem in facial appearance, as well as social and psychological problems in the patient's life. The aim of the present study is to establish clinical evidence of thread-embedding acupuncture (TEA) in the treatment of sequelae of Bell's palsy. Method/Design: This is a patient-assessor blinded, randomized, sham-controlled trial with two parallel arms. Fifty-six patients aged 19–65 years, who have experienced sequel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Another study examined clinical efficacy of thread-embedding acupuncture in fifty-six patients with Bell's palsy sequelae. The authors concluded that threadembedding acupuncture was effective and safe in treatment of Bell'as palsy sequelae 15 . One study examined functional magnetic resonance images to investigate the effect of acupuncture on the functional connectivity of the brain in 28 patients with Bell's palsy and 20 healthy controls.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Another study examined clinical efficacy of thread-embedding acupuncture in fifty-six patients with Bell's palsy sequelae. The authors concluded that threadembedding acupuncture was effective and safe in treatment of Bell'as palsy sequelae 15 . One study examined functional magnetic resonance images to investigate the effect of acupuncture on the functional connectivity of the brain in 28 patients with Bell's palsy and 20 healthy controls.…”
Section: Discussionmentioning
confidence: 98%
“…However, approximately 30% may experience sequelae such as paresis, contracture, facial spasm or synkinesis 12,13,14 . Symptoms of Bell's palsy sequelae are commonly described as synkinesis, contractures, spasm and crocodile tears syndrome, and are rarely described as tears, taste and hearing disorders 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the embedded thread, which is gradually absorbed into the body, causes a long-term therapeutic effect through mechanical and chemical stimulation at the treatment site. 26 In this trial, a STEA needle without the thread will be set as the control intervention, with reference to previous studies 22,27,28 to confirm only the effect of the embedded thread, excluding the stimulation effect of needle insertion. Additionally, to confirm the long-term maintenance effect, 8 weeks of follow-up assessment will be conducted after the end of treatment sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Due to a lack of similar previous studies to act as references, there were many limitations with regard to development of a suitable study protocol. [5] Therefore, to establish robust evidence for the efficacy of TEA to treat FNP, it is necessary to conduct a large-scale, high-quality clinical trial.…”
Section: Introductionmentioning
confidence: 99%